2016
DOI: 10.1080/08941939.2016.1240270
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukin-33 as an Inflammatory Marker in Differential Diagnosis of Idiopathic Granulomatous Mastitis and Breast Cancer

Abstract: The results of our study suggest that measurement of IL-33 and its receptor sST2 levels, alongside radiological studies can help distinguishing IGM from BC. Findings of our study need to be supported with additional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…That is why clinicians usually proceed with repeat biopsies. Therefore, the only way to reach a definitive diagnosis is by obtaining a biopsy [11]. Moreover, histology is a must as radiographic images are nonspecific [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is why clinicians usually proceed with repeat biopsies. Therefore, the only way to reach a definitive diagnosis is by obtaining a biopsy [11]. Moreover, histology is a must as radiographic images are nonspecific [3].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, IL-33 levels if used in conjugation with ultrasound and mammography can favor a diagnosis of IGM. However, the only method for definitive diagnosis at this point remains the use of biopsy [11].…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping analysis showed that there was no significant change in the frequencies of genotypes and alleles at SNPs rs3212227 and rs1929992 in IL-12b and IL-33 genes, respectively, and that serum levels of IL-12 and IL-33 were not influenced by these genotypes in both patients and healthy controls [ 61 ]. Finally, serum IL-33 was used in differential diagnoses of idiopathic granulomatous mastitis (IGM) and breast cancer [ 62 ]. IL-33 was significantly higher in IGM patients as compared to breast cancer patients.…”
Section: The Role Of Il33/st2 In Tumorigenesismentioning
confidence: 99%
“…Although, serum levels of sST2 were significantly lower in IGM patients, there was no significant difference between procalcitonin levels, a clinical marker of inflammation and infection. Thus, serum levels of IL-33 and sST2 could serve as differential diagnostic markers between IGM and breast cancer along with radiological and pathological examinations [ 62 ]. In summary, the IL-33/ST2 pathway promotes progression of breast cancer in both pre-clinical and clinical studies mostly through the recruitment of inflammatory cells that enhance tumor growth, invasiveness, and angiogenesis.…”
Section: The Role Of Il33/st2 In Tumorigenesismentioning
confidence: 99%
“…6 The levels of inflammation biomarkers such as interleukin-33 (IL- 33) and soluble ST2 receptor of IL-33 (sST2) were significantly higher in women with IGM compared with controls. 7 In addition, based on the result of a nested case-control study on 667 women with BPBD and 1321 controls, serum levels of C-reactive protein (CRP) were positively and adiponectin were inversely associated with the early stages of BPBD. 8 In addition to the role of inflammation, other various causes such as endogenous hormones, oral contraceptives, estrogen replacement therapy and dietary intake during adolescence are important factors in the development of BBD.…”
Section: Introductionmentioning
confidence: 99%